Influence of hormones on the immunotolerogenic molecule HLA-G: a cross-sectional study in patients with congenital adrenal hyperplasia. Issue 5 (November 2019) - Nguyen, Lee S; Rouas-Freiss, Nathalie; Funck-Brentano, Christian; Leban, Monique; Carosella, Edgardo D; Touraine, Philippe; Varnous, Shaida; Bachelot, Anne; Salem, Joe-Elie
Abstract : Background: HLA-G is an immune checkpoint molecule, naturally expressed during pregnancy, playing a critical role in the tolerance of the fetal semi-allograft from the maternal immune system. While HLA-G expression levels are associated with progesterone, the influence of other hormones is still unclear. Congenital adrenal hyperplasia (CAH) represents an adequate model to study the hormonal influence on biomarkers as it leads to impaired cortisol biosynthesis and increased progesterone and androgens production due to 21-hydroxylase enzyme deficiency. Methods: In a cross-sectional study of CAH patients matched on sex and age with healthy control, the association between circulating levels of soluble HLA-G and hormones was assessed by use of non-parametric analyses tests. Multivariable linear regressions were performed on normalized data. Results: Overall, 83 CAH patients and 69 healthy controls were included. Among CAH patients, all were under glucocorticoid and 52 (62.6%) were under mineralocorticoid supplementation. Compared to controls, CAH patients had increased HLA-G levels (15 vs 8 ng/mL, P  = 0.02). In controls, HLA-G level was independently associated with progesterone and estradiol (β = 0.44 (0.35–1.27) and −0.44 (−0.94, −0.26) respectively, both P values = 0.001). In CAH patients, HLA-G level was independently associated with mineralocorticoid supplementation dosage (β = 0.25 (0.04–0.41), P  = 0.001) and estradiol (β = −0.22 (−0.57, −0.02), P  < 0.001). Conclusion: CAH patients had higher HLA-G levels than healthy controls. HLA-G level was positively associated with progesterone and corticosteroid supplementation, and negatively with estradiol. The association between mineralocorticoid, renin and HLA-G levels may suggest a role of the renin-angiotensin system in the expression of soluble HLA-G.